2011
DOI: 10.1007/s12350-010-9296-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ischemia on left ventricular dyssynchrony by phase analysis of gated single photon emission computed tomography myocardial perfusion imaging

Abstract: The presence of even a large reversible perfusion defect does not alter the indices of mechanical dyssynchrony by phase analysis. Further, comparable information is obtained whether using a low dose or a high dose of the radiotracer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 17 publications
(23 reference statements)
5
50
1
1
Order By: Relevance
“…This technique is called phase analysis (4). Previous studies (11) have shown that phase analysis is a valuable tool for patient management and diagnosis, especially in cases of heart failure. Another study demonstrated that phase analysis also has incremental value for evaluating ischemic heart disease using thallium-based exercise-induced stress MPI (5).…”
Section: Discussionmentioning
confidence: 99%
“…This technique is called phase analysis (4). Previous studies (11) have shown that phase analysis is a valuable tool for patient management and diagnosis, especially in cases of heart failure. Another study demonstrated that phase analysis also has incremental value for evaluating ischemic heart disease using thallium-based exercise-induced stress MPI (5).…”
Section: Discussionmentioning
confidence: 99%
“…Late post-stress imaging (30-60 minutes), as is the case with Tc-99m SPECT imaging, often results in recovery of LV stunning with no residual detectable change in LV dyssynchrony (stress vs rest) at the time of imaging, even in the presence of large ischemic burden. 24,25 On the other hand, early post-stress imaging that is more feasible with Tl-201 (5-10 minutes) captures stress-induced changes in LV dyssynchrony. 26 Indeed, dyssynchronous contraction in the ischemic region during peak stress, leads to deterioration of LV synchrony as opposed to the normal myocardium that retains its synchrony.…”
Section: See Related Article Pp 1048-1056mentioning
confidence: 99%
“…In a small study, the presence of reversible perfusion defect did not alter the indices of mechanical dyssynchrony by phase analysis from gated SPECT; however, there was no angiographic data to correlate with anatomic stenosis. 11 In a more recent study, patients with multi-vessel CAD confirmed with angiography had significantly more global and territorial dyssynchrony at early post-stress than at rest 201-Thallium SPECT MPI. 12 Another study measured LV synchrony immediately after reperfusion therapy using real-time three-dimensional echocardiography and showed strong correlation with 201-Thallium and 123I-beta methyl-iodophenyl pentadecanoic acid mismatch with dual isotope SPECT, a reflection of acute myocardial stunning.…”
mentioning
confidence: 93%